2015
DOI: 10.4209/aaqr.2013.10.0316
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Health Effects of Particulate Matter: A Comparison between Wood Smoke and Multi-Source Polluted Urban Areas in Chile

Abstract: Temuco and Pudahuel are two urban areas in Chile that are among the highest in particulate matter (PM 10 ) air pollution in Chile. In fact, Temuco is also classified as one of the most polluted cities in Latin America by the World Health Organization. Both cities show important differences in the sources of this PM 10 pollution. For Temuco, a southern city, the main source is the residential wood combustion (RWC), and for Pudahuel, located in the central zone, the main sources are mobile and point sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 85 publications
2
32
0
Order By: Relevance
“…From a health care perspective, the number concentration distribution is critical; this varied depending on the diameter of aerosol particles when chalk was used in the class. Previous studies have demonstrated the health effects of short-or long-term exposure to fine and coarse dust particles (Pope et al, 2004, 200;Pope and Dockery, 2006;Downs et al, 20072;Díaz-Robles et al, 2015). Chalk PM 2.5 could also stimulate alveolar macrophages to produce reactive oxygen species and cause oxidative stress and cytotoxicity (Zhang et al, 2015a, b).…”
Section: Particle Size Distribution Of Chalk Dustmentioning
confidence: 99%
“…From a health care perspective, the number concentration distribution is critical; this varied depending on the diameter of aerosol particles when chalk was used in the class. Previous studies have demonstrated the health effects of short-or long-term exposure to fine and coarse dust particles (Pope et al, 2004, 200;Pope and Dockery, 2006;Downs et al, 20072;Díaz-Robles et al, 2015). Chalk PM 2.5 could also stimulate alveolar macrophages to produce reactive oxygen species and cause oxidative stress and cytotoxicity (Zhang et al, 2015a, b).…”
Section: Particle Size Distribution Of Chalk Dustmentioning
confidence: 99%
“…An analysis of deaths and hospital admissions for cardiovascular and respiratory diseases in two polluted cities in Chile concluded: "there is greater risk when people are exposed to air polluted with wood smoke" (2). For 119 U.S. urban communities: "Ambient levels of elemental carbon (EC) and organic carbon matter (OCM), which are generated primarily from vehicle emissions, diesel, and wood burning, were associated with the largest risks of emergency hospitalization across the major chemical constituents of PM2.5."…”
Section: Pm25 Composition and Health Impactsmentioning
confidence: 99%
“…The statistical model accounted for the effects of temperature, humidity and numbers of visits for influenza. Other pollutants were also considered-similar models were fitted for NO 2 (5), AA activity was not statistically associated with any tested health outcome, but DTT activity was associated with ED visits for both asthma or wheeze and congestive heart failure (7). Accurate estimates of the health effects of air pollution require accurate estimates of pollution exposure, otherwise the effect will be under-estimated (8).…”
Section: Pm25 Composition and Health Impactsmentioning
confidence: 99%
“…Surfaces of these carbonaceous particles provide a platform to intermix with various chemicals such as metals and organics, which can increase the toxicity of the particles. Epidemiological evidence shows that particulate matter (PM) at levels typically found in urban areas are considered to have adverse health effects, including exacerbation of pre-existing respiratory diseases (Kumar et al, 2013;Díaz-Robles et al, 2015). For example, Kumar et al (2013) observed that the 2.3% risk of an acute exacerbation of chronic obstructive pulmonary disease (COPD) could be increased by a unit increase in exposure to PM of less than 2.5 µm in aerodynamic diameter (PM 2.5 ).…”
Section: Introductionmentioning
confidence: 99%